Update on diagnostic testing for platelet function disorders: What is practical and useful?. (8th May 2019) - Hayward, Catherine P. M.; Moffat, Karen A.; Brunet, Justin; Carlino, Stephen A.; Plumhoff, Elizabeth; Meijer, Piet; Zehnder, James L.
Abstract: Introduction: Platelet function disorders (PFD) are an important group of bleeding disorders that require validated and practical laboratory strategies for diagnosis. Methods: This review summarizes the authors' experiences, current literature, and an international survey to evaluate the practices of diagnostic laboratories that offer tests for PFD. Results: Blood counts, blood film review, and aggregation tests are the most commonly performed investigations for PFD and help determine whether there is thrombocytopenia and/or defective platelet function due to a variety of causes. The performance characteristics of tests for PFD, and the level of evidence that these tests detect bleeding problems, are important issues to determine where tests are useful for diagnostic or correlative purposes, or research only uses. Platelet aggregation assays, and quantitative analysis of platelet dense granule numbers, are tests with good performance characteristics that detect abnormalities associated with increased bleeding in a significant proportion of individuals referred for PFD investigations. Lumiaggregometry estimates of platelet adenosine triphosphate release show greater variability which limits the diagnostic usefulness. Diagnostic laboratories report that fiscal and other constraints, including a lack of high‐quality evidence, limit their ability to offer an expanded test menu for PFD. Conclusion: PFD are clinically important bleeding disorders that remain challenging for diagnostic laboratories to investigate. While some PFD tests are well validated for diagnostic purposes, gaps in scientific evidence and resource limitations influence diagnostic laboratory decisions on which PFD tests to offer.